1992
DOI: 10.21273/jashs.117.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Changes and Leaf Blackening in Cut Flower Stems of Protea eximia

Abstract: We tested the hypothesis that premature leaf blackening in cut flower stems of Protea eximia (Salisb. ex Knight) Fourcade may be brought about by a low leaf carbohydrate status. Leaves on cut flower stems held in darkness blackened within 4 days, whereas those on stems held in a greenhouse remained healthy for 5 days. Leaf blackening was also retarded by supplying 1% sucrose in the vase solution; but other additives (hypochlorite, silver thiosulfate, bisulfite) were not effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 11 publications
3
25
0
Order By: Relevance
“…Alternatively, considering that starch has minimal osmotic activity (Setter, 1990), the rapid rate of starch hydrolysis in response to sink demand may impose osmotic stress on leaf cells. It has been suggested that the sugar alcohol, polygalatol, may be involved in cellular osmotic adjustment during stress, since it does not decline under depleted carbohydrate conditions (Bieleski et al, 1992;McConchie and Lang, 1993b), as would be expected if it were involved in growth and maintenance metabolism (Cheeseman, 1988). Instead, concentrations either increase slightly or remain stable (Table 1) (Bieleski et al, 1992;McConchie and Lang, 1993b;McConchie et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, considering that starch has minimal osmotic activity (Setter, 1990), the rapid rate of starch hydrolysis in response to sink demand may impose osmotic stress on leaf cells. It has been suggested that the sugar alcohol, polygalatol, may be involved in cellular osmotic adjustment during stress, since it does not decline under depleted carbohydrate conditions (Bieleski et al, 1992;McConchie and Lang, 1993b), as would be expected if it were involved in growth and maintenance metabolism (Cheeseman, 1988). Instead, concentrations either increase slightly or remain stable (Table 1) (Bieleski et al, 1992;McConchie and Lang, 1993b;McConchie et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Premature leaf blackening in many cut flower Protea species seriously reduces vase life and market value. When stems are held under dark postharvest conditions, blackening symptoms can appear within 3 days after harvest (Bieleski et al, 1992;McConchie et al, 1991). The current hypothesis suggests that postharvest leaf blackening in Protea is induced by a sequence of metabolic events associated closely with senescence, beginning with the total depletion of leaf carbohydrates and followed by subsequent hydrolysis of intercellular membranes to supply respiratory substrate for the developing inflorescence (Ferreria, 1986).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Simple carbohydrates can be distinguished by thin layer chromatography (Petrovic & Canic, 1969;Washuttl et al, 1973;Webb & Burley, 1962), gas chromatography (GC) (Makinen & Soderling, 1980;Megias-Perez et al, 2014;Sanz et al, 2004;Wrolstad, Culbertson, Nagaki, & Madero, 1980), and high performance liquid chromatography (HPLC) (Bieleski, Ripperda, Newman, & Reid, 1992;Cantin et al, 2009;Fan-Chiang & Wrolstad, 2010;Durst et al, 1995;Ellefson, 2005;Muir et al, 2009;Spanos & Wrolstad, 1987;Usenik, Fabcic, & Stampar, 2008;Zhou et al, 2012). These analyses and methods have been well summarised in Brummer and Cui (2005), De Goeij (2013), Ellefson (2005), Muir et al (2009), andMartinez-Castro (2007) regarding the specific advantages and pitfalls of each separation technique.…”
Section: Analysing For Simple Carbohydrate In Fruit and Fruit Productsmentioning
confidence: 99%
“…Their removal can be accomplished by several methods, including ion exchange or reversed phase sorbent mini-columns (Ballistreri et al, 2013;Cantin et al, 2009;Durst et al, 1995;Fan-Chiang & Wrolstad, 2010;Liu et al, 1999;Muir et al, 2009;Spanos & Wrolstad, 1987;van Gorsel et al, 1992), syringe filters containing nylon, PVP (polyvinylpyrrolidone), etc. (Ledbetter et al, 2006;Lee et al, 2009), or PVP and PVPP (polyvinylpolypyrrolidone) powders alone (added directly to sample; Bieleski et al, 1992;Cornwell et al, 1981). Sample preparations prior to carbohydrate analysis were well reviewed by Sanz and Martinez-Castro (2007).…”
Section: Analysing For Simple Carbohydrate In Fruit and Fruit Productsmentioning
confidence: 99%